Korzyść z ponownej lektury tekstów o folklorze autorstwa profesor Kazimiery Zawistowicz-Adamskiej - Wieruszewska, Maria (Zeszyty Wiejskie, 2017)
The paper presents and analyses views of the scholar, ethnographer and founder of the so-called Łódź school of ethnography, Kazimiera Zawistowicz-Adamska (1897–1984) concerning the issues of cognitive difficulties they encountered – as well as some that are still experienced by folklore researchers. While perceiving a close relationship between folklore and folk artistic culture this scholar emphasized the extent of studies devoted to these issues in the global science and their popularity in non-scientific circles. Simultaneously, she presented an opinion that ethnographers should not be constrained to studies on so-called material culture that is always conditioned socially and always appears in the context of phenomena (fairly conventionally) of both, social and spiritual culture. Thus, the scholar’s standpoint functions as a kind of conciliation for op-posing standpoints – supporters of things, on the one hand, and defenders of symbols on the other.